Analysis of Employee Self-Development Need in the Era of Digitization - Gimin Gimin; Sri Kartikowati (Universitas Negeri Padang, 2024)
This research aimed to analyze employees’ self-development needs during information digitization, specifically in the Faculty of Teacher Training and Education (FKIP) Riau University. Data were collected using Google Form questionnaire, obtaining a 79.03% response rate. The data collected were analyzed using descriptive statistics and regression analyses. The result showed that (1) Most employees had a strong understanding of primary duties and functions, suggesting a